Ensuring successful implementation of communication-and-resolution programmes. Issue 11 (20th January 2020) - Mello, Michelle M; Roche, Stephanie; Greenberg, Yelena; Folcarelli, Patricia Henry; Van Niel, Melinda Biocchi; Kachalia, Allen
Abstract : Background: Communication-and-resolution programmes (CRP) aim to increase transparency surrounding adverse events, improve patient safety and promote reconciliation by proactively meeting injured patients' needs. Although early adopters of CRP models reported relatively smooth implementation, other organisations have struggled to achieve the same. However, two Massachusetts hospital systems implementing a CRP demonstrated high fidelity to protocol without raising liability costs. Study question: What factors may account for the Massachusetts hospitals' ability to implement their CRP successfully? Setting: The CRP was collaboratively designed by two academic medical centres, four of their community hospitals and a multistakeholder coalition. Data and methods: Data were synthesised from (1) key informant interviews around the time of implementation and 2 years later with individuals important to the CRP's success and (2) notes from 89 teleconferences between hospitals' CRP implementation teams and study staff to discuss implementation progress. Interview transcripts and teleconference notes were analysed using standard methods of thematic content analysis. A total of 45 individuals participated in interviews (n=24 persons in 38 interviews), teleconferences (n=32) or both (n=11). Results: Participants identified facilitators of the hospitals' success as: (1) the support of top institutional leaders, (2) heavy investments in educating physicians about the programme, (3) active cultivation of the relationship between hospital risk managers and representatives from the liability insurer, (4) the use of formal decision protocols, (5) effective oversight by full-time project managers, (6) collaborative group implementation, and (7) small institutional size. Conclusion: Although not necessarily causal, several distinctive factors appear to be associated with successful CRP implementation.